Reducing health inequalities through general practice: a realist review and action framework - Anna Gkiouleka; Geoff Wong; Sarah Sowden; Isla Kuhn; Annie Moseley; Sukaina Manji; Rebecca R Harmston; Rikke Siersbaek; Clare Bambra; John A Ford (NIHR Journals Library, 2024)
Background Socio-economic inequalities in health have been in the public agenda for decades. General practice has an influential role to play in mitigating the impact of inequalities especially regarding chronic conditions. At the moment, general practice is dealing with serious challenges in relation to workforce shortages, increasing workload and the impact of the COVID-19 pandemic. It is important to identify effective ways so that general practice can play its role in reducing health inequalities. Objectives We explored what types of interventions and aspects of routine care in general practice decrease or increase inequalities in health and care-related outcomes. We focused on cardiovascular disease, cancer, diabetes and/or chronic obstructive pulmonary disease. We explored for whom these interventions and aspects of care work best, why, and in what circumstances. Our main objective was to synthesise this evidence into specific guidance for healthcare professionals and decision-makers about how best to achieve equitable general practice. Design Realist review. Main outcome measures Clinical or care-related outcomes by socio-economic group, or other PROGRESS-Plus criteria. Review methods Realist review based on Pawson's five steps: (1) locating existing theories, (2) searching for evidence, (3) selecting articles, (4) extracting and organising data and (5) synthesising the evidence. Results Three hundred and twenty-five studies met the inclusion criteria and 159 of them were selected for the evidence synthesis. Evidence about the impact of general practice interventions on health inequalities is limited. To reduce health inequalities, general practice needs to be: connected so that interventions are linked and coordinated across the sector; intersectional to account for the fact that people's experience is affected by many of their characteristics; flexible to meet patients' different needs and preferences; inclusive so that it does not exclude people because of who they are; community-centred so that people who receive care engage with its design and delivery. These qualities should inform action across four domains: structures like funding and workforce distribution, organisational culture, everyday regulated procedures involved in care delivery, interpersonal and community relationships. Limitations The reviewed evidence offers limited detail about the ways and the extent to which specific interventions increase or decrease inequalities in general practice. Therefore, we focused on the underpinning principles that were common across interventions to produce higher-level, transferrable conclusions about ways to achieve equitable care. Conclusions Inequalities in general practice result from complex processes across four different domains that include structures, ideas, regulated everyday procedures, and relationships among individuals and communities. To achieve equity, general practice needs to be connected, intersectional, flexible, inclusive and community-centred. Future work Future work should focus on how these five essential qualities can be better used to shape the organisational development of future general practice. Study registration This trial is registered as PROSPERO CRD42020217871. Funding This award was funded by the National Institute for Health and Care Research (NIHR) Health and Social Care Delivery Research programme (NIHR award ref: NIHR130694) and is published in full in Health and Social Care Delivery Research; Vol. 12, No. 7. See the NIHR Funding and Awards website for further award information. Plain language summary Health inequalities are unfair differences in health across different groups of the population. In the United Kingdom, the health inequality gap in life expectancy between the richest and poorest is increasing and is caused mostly by differences in long-term conditions like cancer and cardiovascular disease and respiratory conditions, such as chronic obstructive pulmonary disease. Partly National Health Service inequalities arise in delays in seeing a doctor and care provided through doctors' surgery, such as delays in getting tests. This study explored how general practice services can increase or decrease inequalities in cancer, cardiovascular disease, diabetes and chronic obstructive pulmonary disease, under what circumstances and for whom. It also produced guidance for general practice, both local general practices and the wider general practice system, to reduce inequalities. We reviewed existing studies using a realist methodology. This methodology helps us understand the different contexts in which interventions work or not. We found that inequalities in general practice result from complex processes across different areas. These include funding and workforce, perceptions about health and disease among patients and healthcare staff, everyday procedures involved in care delivery, and relationships among individuals and communities. To reduce inequalities in general practice, action should be taken in all these areas and services need to be connected (i.e. linked and coordinated across the sector), intersectional (i.e. accounting for the fact that people's experience is affected by many of their characteristics like their gender and socio-economic position), flexible (i.e. meeting patients' different needs and preferences), inclusive (i.e. not excluding people because of who they are) and community-centred (i.e. working with the people who will receive care when designing and providing it). There is no one single intervention that will make general practice more equitable, rather it requires long-term organisational change based on these principles. Scientific summary Background Socio-economic inequalities in health have been in the public health discourse and policy agenda for decades. There is ample evidence showing that inequalities in premature mortality are mainly driven by inequalities in chronic diseases and especially cancer, cardiovascular and respiratory disease. In the most deprived areas of the country, patients with cardiovascular disease (CVD) deal with a four times higher possibility of premature death than patients in the least deprived areas. In this context, general practice as the front door to the healthcare system has an important role to play in reducing inequalities especially when it comes to chronic conditions. The COVID-19 pandemic has highlighted both the range of health inequalities and the importance of general practice in addressing and tackling the problem. However, it has also revealed chronic deficiencies of the sector which combined with the pressure during the pandemic have resulted in a physically and emotionally exhausted workforce and greater scarcity of resources. In this climate, there is an urgent need for action to secure general practice's future as more equitable and effective for its patients, their families and carers, but also for its workforce. Objectives Our study explored what types of interventions and aspects of routine care in general practice decrease or increase inequalities in healthcare and outcomes among people with or at risk of CVD, cancer, diabetes and/or chronic obstructive pulmonary disease, and for whom these interventions and aspects of care work best, why, and in what circumstances. Our main objective was to synthesise this evidence to produce specific guidance for healthcare professionals and decision-makers about how best to tackle health inequalities in general practice. Methods We conducted a realist review following Pawson's five iterative steps: (1) locating existing theories, (2) searching for evidence, (3) selecting articles, (4) extracting and organising data and (5) synthesising the evidence. We started with an exploratory literature search and discussions with experts in the field, to identify existing theories that explain how, for whom, why and in what circumstances interventions or care delivered in general practice may increase or decrease health inequalities. Next, we conducted a literature review in two steps.